Substitusi Bahan Acid dan Reactive Dyestuff dalam Metode Pewarnaan Kulit Domba Wet Blue Untuk Kulit Nappa dan Suede Garmen Terhadap Ketahanan Cuci Air Sebagai Upaya Pengelolaan Laboratorium - Armila Zahra Tawarniate; Tantri Fauziah (Politek ATK Yogyakarta Press, 2025)
To test the effect of different dyeing method on chrome - leather wet blue using reactive and acid dyes. Attempts were made to obtain a dyeing method that is as a new alternative, especially for skin that require high- wash durability. It is expected that the new method with the application of reactive dyes will result in the washing of the leather resistance levels were very good compared with the conventional method using acid dyes. Methodology research using wet blue sheepskin random quality, as many as 12 pieces taken at random from the bath chrome tanning process, split into 24 parts of the back (side) . Skin re- randomized and numbered 1-24 . Number 1-12 wet blue leather is treated with a reactive dyestuff, for this kind of napa and suede garment, different colors such as black, red, blue, yellow. Skin numbers 13-24 is dyed by acid dyestuff with the same color such as black, red, blue, and yellow. Statistical analysis using the General Linear Model Univariate , with three independent variables , the type of dye , colors and type of leather. Dependent variable is washing fastness.. Analysis using SPSS 15, F test - significances at 95% confidence level. Reactive dyestuff has the resilience washing (washing fastness), different from acid dyestuff. In the test values ​​F = 346.931, and the number of significance < 0.05. Average washing durability reactive dyestuff has better washing fastness than with acid dyestuff. The black color has a lower washing resistance, and the color yellow has a higher resistance. Skin type (Napa, suede , upholstery ) have different resistance that does not wash.